Rizobakteri Antagonis Sebagai Agen Biokontrol Fusarium oxysporum f.sp. capsici Penyebab Layu Fusarium Pada Cabai Merah (Capsicum annuum L.) - Selviana Anggraini; Rahil Ade Rifqah; Pajri Ananta Yudha; Dini Puspita Yanty; Poppy Khairunnisa; Sumini; Aslan Sari Thesiwati (University of Prof. Dr. Hazairin, SH, 2026)
Fusarium wilt caused by Fusarium oxysporum f.sp. capsici is one of the most destructive diseases affecting red chili pepper cultivation because it significantly reduces plant growth and yield. Disease management that still relies on synthetic fungicides may increase environmental pollution and promote pathogen resistance; therefore, environmentally friendly control alternatives are required. This study aimed to evaluate the effectiveness of several local rhizobacterial isolates as antagonistic agents against Fusarium wilt in red chili pepper. The novelty of this study lies in the evaluation of indigenous rhizobacterial isolates with dual functions as antagonistic agents against Fusarium oxysporum f.sp. capsici and as plant growth-promoting rhizobacteria (PGPR) capable of enhancing red chili pepper growth under both in vitro and in vivo conditions. The results showed that all rhizobacterial isolates significantly inhibited pathogen growth. Isolate UBI-Rz04 exhibited the highest inhibition rate of 85.78% and the lowest fungal biomass (0.03 g) under in vitro conditions. In the in vivo assay, isolate UBI-Rz01 reduced disease incidence to 44.67%, compared with 80.00% in the control, and suppressed the pathogen population to 3.33 × 10⁵ CFU/g soil. Rhizobacterial application also improved red chili pepper growth. These findings indicate that local rhizobacteria have strong potential as environmentally friendly biological control agents for sustainable red chili pepper cultivation.